The Technique of Frame Coaching – A Brief Life Coaching Goal-Directed Method - LeBlanc, Bruce D. (Technium Social Sciences Journal, 2022)
Frame Coaching is an efficacious brief life coaching method. Drawing upon Erving Goffman’s Frame Analysis, Frame Coaching adapts its application through the utilization of a literal framing process. Through framing, individuals visualize an orientation that facilitates the articulation of a goal and then undertake goal action steps toward goal achievement. Goal articulation is for an autonomously generated and self-articulated life issue. Frame Coaching also draws upon the psychological orientations of humanistic, cognitive, and solution-focused psychology, allowing for a life-coach strengths-based approach within the existential nature of life coaching.